Reaching UiTM community, newly registered postgraduate students and public through PG4U - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
IPSis welcomes new postgraduate students registering for the March 2023 intake, UiTM community and the public through the Online MS Team platform. The Recruitment and Admission, Academic, Research and Coursework as well as the Management Team were part of the welcoming staff to ensure information related to postgraduates was successfully delivered and also provided the best hospitality to the 300 participants who joined the briefing session.